Migration and Speciation of Lead and Copper in a River System Polluted from a Chloralkali Plant - Dey, G.; Sarin, R. (Asian Journal of Chemistry, 2010)
The analytical scheme proposed in this paper can be applied for speciating chloralkali plant effiuents and the receiving river water body.